The Equine Gingiva: A Histological Evaluation - Steinfort, Saskia; Röcken, Michael; Vogelsberg, Jörg; Failing, Klaus; Staszyk, Carsten (Frontiers in Veterinary Science, 2019)
Equine periodontal disease (ePD) in horses has long been recognised as a painful disease, leading to a poor condition. The disease is widespread and attracts growing attendance in equine dental medicine. The understanding of the underlying aetiological and pathological mechanisms of ePD is necessary to develop effective prophylactic and treatment options. As a first step, a thorough description of the histological features of the healthy equine gingiva is required. Specimens were taken from six horses (3 mares, 3 geldings, age: 0.5–26 years). The animals were euthanised for reasons not related to this study. Heads were dissected and gingival specimens, including parts of the adjacent teeth, alveolar bone and the periodontal ligament, were obtained from several positions of the dentition. After decalcification, the specimens were embedded in paraffin wax and serial sections were stained. Sections were evaluated via light microscopy, with special attention to the structural components of the gingiva, i.e. the gingival sulcus, the epithelium and the components of the lamina propria (LP). Although the equine gingiva showed the same structural components as described in humans and dogs, the equine junctional epithelium was adapted to the equine dental anatomy and attached to the equine-unique peripheral cementum. Leucocytic infiltrations (LI) of the LP, sulcular epithelium (SE) and junctional epithelium (JE) were frequently seen. The amount of LI was not associated with a macroscopically visual pathology (e.g. diastema or food entrapment) in the respective position. The gingival sulcus depth had an average depth of < 1mm.